Smooth Muscle Cell–Derived Interleukin-17C Plays an Atherogenic Role via the Recruitment of Proinflammatory Interleukin-17A+ T Cells to the Aorta. Issue 8 (August 2016) - Butcher, Matthew J.; Waseem, Tayab C.; Galkina, Elena V.
Abstract : Objective—: Atherosclerosis is characterized by frequent communication between infiltrating leukocytes and vascular cells, through chemokine and cytokine networks. Interleukin-17C (IL-17C) is detectable within atherosclerotic lesions; however, the potential involvement of this cytokine has not been examined. Thus, we sought to investigate the role of IL-17C in atherosclerosis. Approach and Results—: The expression of IL-17 cytokines was profiled within aortas of apolipoprotein E double knockout ( Apoe −/− ) mice, and Il17c expression was elevated. Flow cytometry experiments revealed a major population of aortic IL-17C–producing smooth muscle cells. Next, we generated Il17c −/− Apoe −/− mice and demonstrated that atherosclerotic lesion and collagen content was diminished within Western diet–fed Il17c −/− Apoe −/− aortas and aortic roots in comparison to Apoe −/− controls. Smooth muscle cells and fibroblasts were mainly responsible for the reduced Col1A1 expression in the aorta of Il17c −/− Apoe −/− mice. Importantly, IL-17C–treated Apoe −/− aortas showed upregulated Col1A1 expression ex vivo. Il17c −/− Apoe −/− mice displayed a proportional reduction in aortic macrophages, neutrophils, T cells, T helper 1 cells, and T regulatory cells, without corresponding changes in the peripheral immune composition. Examination of aortic IL-17A + T-cell receptor γδ T cells and Th17 cells demonstrated a stark reduction in the percentage and number of these subsets within Il17c −/− Apoe −/− versus Apoe −/− mice. Explanted 12-week Western diet–fed Apoe −/− aortas treated with IL-17C resulted in the induction of multiple vascular chemokines and cytokines. Th17 cells demonstrated attenuated migration toward supernatants from cultures of Il17c −/− Apoe −/− smooth muscle cells, and short-term homing experiments revealed diminished recruitment of Th17 cells to the aorta of Il17c −/− Apoe −/− recipients. Conclusions—: Smooth muscle cell–derived IL-17C plays a proatherogenic role by supporting the recruitment of Th17 cells to atherosclerotic lesions. Abstract : Supplemental Digital Content is available in the text.